2007
DOI: 10.1021/ma071089x
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Responsive Swelling Properties of Polyacrylamide/Poly(acrylic acid) Interpenetrating Polymer Network Nanoparticles

Abstract: Interpenetrating polymer network (IPN), random copolymer, and homopolymer nanoparticles of acrylamide and acrylic acid were prepared using an inverse emulsion polymerization technique. Differential scanning calorimetry and Fourier-transform infrared spectroscopy were used to examine the molecular structure of the prepared polymeric nanoparticles. The spherical morphology and size (∼250 nm diameter) of the nanoparticles was confirmed using scanning electron microscopy. Dynamic light scattering was used to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 34 publications
5
99
0
Order By: Relevance
“…This positive thermo-sensitive volume-phase transition (UCST) can be attributed to the hydrogen-bonding driving forces between the polymers chains as it has been previously reported for interpenetrated P(AAm/AAc) networks. [28,29] At low temperatures, hydrogen-bonding forces between the PAAm and PAAc dominate and maintain the particles in a collapsed state, however, as the temperature increases these bonds weaken and break, which provokes the swelling of the microgel. In our case, because of the low AAc content in the copolymer it is not possible to monitor the formation and breakage of hydrogen bonding either by NMR or IR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This positive thermo-sensitive volume-phase transition (UCST) can be attributed to the hydrogen-bonding driving forces between the polymers chains as it has been previously reported for interpenetrated P(AAm/AAc) networks. [28,29] At low temperatures, hydrogen-bonding forces between the PAAm and PAAc dominate and maintain the particles in a collapsed state, however, as the temperature increases these bonds weaken and break, which provokes the swelling of the microgel. In our case, because of the low AAc content in the copolymer it is not possible to monitor the formation and breakage of hydrogen bonding either by NMR or IR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Poly(acrylamide)/poly(acrylic acid) microgels have been recently described, among others, by Bouillot and Vincent and Peppas and co-workers as systems with positive thermosensitivity. [28,29] Their UCST is associated with the breakage of polymer-polymer hydrogen bonds. [30] In this work, we report on the development of positive thermoresponsive or UCST-type responsive hybrid microgels and describe both the encapsulation of gold nanoparticles in poly(acrylamide-acrylic acid) (P(AAm/AAc)) microgels and the effect of the nanoparticles on the thermosensitivity, morphology, and optical properties of the microgel.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the band appeared at 1035 cm -1 is characteristic for bending vibration of OH group. The band at 1627 Cm -1 related to the overlap stretching vibration of carbonyl group from NIPAm as well as the NH bending [22]. The results show that a crosslinking reaction occurs between ECH and the hydroxyl groups of PVA with the hydrolyzed amide group of AAm which copolymerized with NIPAm.…”
Section: Synthesis and Characterization Of Pva/p(aam-nipam) Nanogelsmentioning
confidence: 86%
“…As a result, the polymer exhibits a random-coil morphology. [132][133] While the preparation of macroscopic hydrogels from these materials was achieved by hydrophobic association crosslinking by Yang et al, 134 the transfer of this concept to the nanoscale was recently demonstrated by Echeverria et al by radical crosslinking copolymerization of acrylamide with acrylic acid in the presence of N,N'-methylenebis(acrylamide) in inverse emulsion. 135 Microgels prepared by this synthetic pathway represent an interesting alternative to the widely examined systems exhibiting a negative volume phase transition.…”
Section: Temperature-sensitive Microgelsmentioning
confidence: 99%